Islamic Education and Digital Technology Disruption: Learning Dynamics, Ethics, and Social Transformation - Zarkoni; Moh. Affan; Abd. Somad; Ahmad Basuni; Hasbullah; Hamdan; Rahmat Zubandi Thahir (DAAR EL-MAKRIFAH: Journal of Islamic Religious Education, 2026)
This study examines the relationship between Islamic education and the challenges of digital technology in the contemporary era. The rapid development of digital technology, including the internet, social media, Artificial Intelligence (AI), and online learning platforms, has significantly transformed educational paradigms, learning systems, and the transmission of religious knowledge. Using a qualitative design with a library research approach, this study analyzed books, scholarly journal articles, and academic publications related to Islamic education, digital transformation, digital literacy, and educational ethics. The findings indicate that digital technology provides substantial opportunities for Islamic education, particularly in expanding access to Islamic scholarship, improving learning effectiveness, encouraging pedagogical innovation, and supporting personalized learning through AI-based applications. Digital platforms, gamification, interactive media, and Learning Management Systems (LMS) positively contribute to student engagement, creativity, and independent learning. However, the study also reveals that digital transformation presents multidimensional challenges, including epistemological crises related to religious authority, the spread of misinformation, moral degradation in digital spaces, reduced teacher-student interaction, psychological pressures on educators, and unequal access to technology. The findings further demonstrate that the successful transformation of Islamic education requires the integration of technology with the principles of tauhid, adab, and maqāṣid al-sharī‘ah. Curriculum reconstruction, strengthening digital literacy, improving teacher competence as “digital murabbi,” visionary leadership, and adaptive institutional policies are essential strategies for responding to technological disruption. This study concludes that digital technology should function not merely as a technical instrument but as a means of strengthening spiritual values, moral character, and humanistic education in contemporary Islamic society.